Transcriptional Regulation of the Glucose-6-Phosphate/Phosphate Translocator 2 Is Related to Carbon Exchange Across the Chloroplast Envelope - Weise, Sean E.; Liu, Tiffany; Childs, Kevin L.; Preiser, Alyssa L.; Katulski, Hailey M.; Perrin-Porzondek, Christopher; Sharkey, Thomas D. (Frontiers in Plant Science, 2019)
The exchange of reduced carbon across the inner chloroplast envelope has a large impact on photosynthesis and growth. Under steady-state conditions it is thought that glucose 6-phosphate (G6P) does not cross the chloroplast membrane. However, growth at high CO2, or disruption of starch metabolism can result in the GPT2 gene for a G6P/Pi translocator to be expressed presumably allowing G6P exchange across the chloroplast envelope. We found that after an increase in light, the transcript for GPT2 transiently increases several hundred-fold within two hours in both the Col-0 and WS ecotypes of Arabidopsis thaliana. The increase in transcript for GPT2 is preceded by an increase in transcript for many transcription factors including Redox Responsive Transcription Factor 1 (RRTF1). The increase in GPT2 transcript after exposure to high light is suppressed in a mutant lacking the RRTF1 transcription factor. The GPT2 response was also suppressed in a mutant with a T-DNA insert in the gene for the triose-phosphate/Pi translocator (TPT). However, plants lacking TPT still had a robust rise in RRTF1 transcript in response to high light. From this we conclude that both RRTF1 (and possibly other transcription factors) and high amounts of cytosolic triose phosphate are required for induction of the expression of GPT2. We hypothesize that transient GPT2 expression and subsequent translation is adaptive, allowing G6P to move into the chloroplast from the cytosol. The imported G6P can be used for starch synthesis or may flow directly into the Calvin-Benson cycle via an alternative pathway (the G6P shunt), which could be important for regulating and stabilizing photosynthetic electron transport and carbon metabolism.